Religious Tolerance in War Takjil Content on TikTok @eloardoaruanse: A Virtual Ethnographic Study - Puspitasari, Euis Evi; Tiur Maida, Marcellista; Kurniadi, Endrian (Jogjakarta Communication Conference (JCC), 2025)
The "War Takjil" phenomenon, a viral trend during the Ramadan month in Indonesia, has become a powerful symbol of interfaith cooperation and tolerance, particularly among younger generations. This study investigates the role of TikTok in fostering religious tolerance during Ramadan 2024 by analyzing viral "War Takjil" content that promotes inclusivity and humor among different religious communities. Adopting a qualitative research approach, this study uses virtual ethnography to analyze TikTok videos and audience interactions, exploring how these videos communicate messages of unity and coexistence. Findings reveal that TikTok videos focusing on cross-religious participation in "War Takjil" use humor and shared traditions to break down barriers and create spaces for respectful dialogue. This study argues that TikTok, with its interactive and engaging format, is an effective platform for promoting religious tolerance, offering new insights into how digital media can foster social change and cultural understanding.